A multiplex oligonucleotide ligation-PCR method for the genoserotyping of common Salmonella using a liquid bead suspension assay. (May 2020) - Gand, Mathieu; Mattheus, Wesley; Roosens, Nancy H.C.; Dierick, Katelijne; Marchal, Kathleen; De Keersmaecker, Sigrid C.J.; Bertrand, Sophie
Abstract: Salmonella is a major pathogen having a public health and economic impact in both humans and animals. Six serotypes of the Salmonella genus are mentioned in the Belgian and European regulation as to be rapidly excluded from the food chain (EU regulation N°2160/2003, Belgian royal decree 27/04/2017). The reference method for Salmonella serotyping, including slide-agglutination and biochemical tests, is time-consuming, expensive, not always objective, and therefore does not match the fast identification criteria required by the legislation. In this study, a molecular method, using genetic markers detected by Multiplex Oligonucleotide Ligation – PCR and Luminex technology, was developed for the identification of the 6 Salmonella serotypes and their variants subjected to an official control. The resulting method was validated with the analysis of 971 Salmonella isolated from different matrixes (human, animal, food or environment) and 33 non- Salmonella strains. The results were compared with the reference identifications, achieving an accuracy of 99.7%. The cost-effective high-throughput genoserotyping assay is performed in 1 day and generates objective results, thanks to the automatic interpretation of raw data using a barcode system. In conclusion, it is fully adapted to the implementation in first line laboratories and meets the requirements of the regulation. Highlights: The Salmonella serotyping by slide agglutination is complex and not objective. A new molecular method for genoserotyping was developed based on molecular markers. The developed method validated with the analysis of 1004 confirmed isolates. A barcode system gives clear and objective interpretation of identification results. Fast and cost effective identification of important Salmonella serotypes in routine.